The Concept of ‘States within a State’ Amidst Conflict and Peace Building Ventures In Bafut (Global Journal of Human-Social Science, 2023)
This study looks at the perception and manifestation of the concept of states in African communities A state in African context is an organisation of human beings connected by a system of relations Within the states different groups of people exist and different individuals have different roles to play Some exercise special powers or authority capable of giving command which is obeyed by the people they rule In the Bamenda Grassfields of Cameroon present-day North West Region these individuals are called fons and chiefs and they rule fondoms In Westernised societies they would be called kings Since colonial period government administrators refer to them as traditional rulers or natural rulers Amongst these rulers are some who rule over what is commonly referred to as semi-autonomous polities within the fondoms
Keywords: states; conflict; peace building; bafut; cameroon